The Role of Probiotics as Adjuvant Therapy for Irritable Bowel Syndrome in Children - Ananda Rizky (Riviera Publishing, 2025)
Irritable Bowel Syndrome (IBS) is a functional gastrointestinal disorder (GGIF) that is not caused by disease or organ damage. The exact pathophysiological mechanisms underlying IBS are still unknown. The pathogenesis of IBS involves alterations of gastrointestinal motility, post-infection reactivity, visceral hypersensitivity, gut-brain interactions, microbiota dysbiosis, bacterial overgrowth in the small intestine, sensitivity to food, carbohydrate malabsorption, and intestinal inflammation. Evidence of the efficacy of most pharmacological treatments for IBS is still weak, leading to unsatisfactory symptom control or the possibility of adverse reactions in many patients. The method of writing this article is in the form of a narrative review from various sources including google scholar, PubMed, and science direct with the keywords